Supplementation of patients with sickle cell disease with astaxanthin increases plasma- and erythrocyte-astaxanthin and may improve the hemolytic component of the disease - Ruiz-Núñez, Begoña; Rooij, Stéphanie A. De; Offringa, Pieter J.; Schuitemaker, Gert E.; Teerlink, Tom; Booi, Hose S.M.; Dijck-Brouwer, Janneke D.A.; Muskiet, Frits A.J. (Free Radicals and Antioxidants)
Aim & background: Sickle cell disease (SCD) is characterized by hemolytic and vaso-occlusive compo- nents. Astaxanthin is a carotenoid of marine origin, without pro-oxidant properties. Methods: In this open label pilot study, we investigated whether orally administered astaxanthin in- corporates into erythrocytes (RBC) of SCD patients and studied the effect on hematological and clinical chemical parameters. Ten SCD patients (6e52 years) in Sint Maarten received 8e12 mg astaxanthin during 3 months. Results: Baseline plasma- (33 nmol/L) and RBC- (11 nmol/L packed RBC) astaxanthin increased to 225, 174, 167 nmol/L (plasma) and 149, 100, 71 nmol/L packed RBC at 1e3 months, respectively. Reticulocytes decreased from baseline and 2 months (9.5 and 8.8%) to 3 months (5.6%), MCV from 2 to 3 months (88 e86 fL), MCH from baseline to 3 months (30e28 pg) and RDW from baseline and 2 months (19.2 and 19.0%) to 3 months (16.7%). Plasma arginine decreased from 2 to 3 months (46.6e39.4 mmol/L). Asym- metric dimethylarginine (ADMA) did not change. Reticulocytes at baseline correlated with relative changes in reticulocytes from baseline to 3 months. Relative changes in reticulocytes correlated with relative changes in RBC, RDW, LDH, ALAT, but not hematocrit, within the same period. Conclusion: Astaxanthin incorporates into SCD RBC and may favorably affect the hemolytic component. A larger randomized controlled trial is indicated, using similar or higher dose, preferably during more than 3 months, concomitant with (other) low dose antioxidants (vitamin E, beta-carotene, vitamin C, folic acid), minerals (zinc, if necessary, selenium), arginine, fish oil and vitamin D.
Keywords: Antioxidant; Hemolytic component; Reticulocytes; Arginine; Asymmetric dimethylarginine